Fitness costs of Cry1F resistance in fall armyworm, Spodoptera frugiperda. (28th November 2013) - Vélez, A. M.; Spencer, T. A.; Alves, A. P.; Crespo, A. L. B.; Siegfried, B. D.
Abstract Transgenic corn, Zea mays L., expressing the Bacillus thuringiensis Berliner (Bt) protein Cry1F has been registered for Spodoptera frugiperda (J. E. Smith) control since 2003 in the USA. Unexpected damage to Cry1F corn was reported in 2006 in Puerto Rico, and Cry1F resistance in S. frugiperda from Puerto Rico was documented. The study of fitness costs associated with insect resistance to Bt insecticidal proteins is important for understanding resistance evolution and for evaluating resistance management practices used to mitigate resistance to transgenic corn. Currently, no studies have addressed the fitness costs associated with Cry1F resistance in S. frugiperda. In this study, susceptible and resistant strains with similar genetic background and their reciprocal crosses were used to estimate Cry1F resistance fitness costs. Comparisons between life‐history traits and population growth rates of homozygous susceptible, heterozygous and homozygous resistant S. frugiperda were used to determine whether the resistance is associated with fitness costs. Major fitness costs were not apparent in either heterozygotes or homozygous resistant insects. However, there was a slight indication of hybrid vigour in the heterozygotes. Additionally, two lines in which the frequency of the resistant alleles was fixed at 0.5 were followed for seven generations, after which the frequency of resistant alleles slightly decreased in both lines. The lack of strong fitness costs associated with Cry1F resistance in S. frugiperda indicates that initial allele frequencies may be higher than expected in field populations and will tend to remain stable in field populations in the absence of selection pressure (e.g. Puerto Rico).